Optimalisasi Peran Pejabat Pembuat Komitmen dalam Pelaksanaan Pengadaan Barang/ Jasa Pemerintah di Provinsi Nusa Tenggara Timur - Mudak, Saul Davi (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2022)
This study aims to find out and explain how to increase the role of the Commitment Making Officer (CMO) so that it is more optimal in the implementation of government procurement of goods/services in East Nusa Tenggara Province. The research method uses a qualitative method with an exploratory approach where researchers seek to find more complete and detailed information about a topic or problem that has not been reached. The results of this study indicate that by optimizing the role of CMO through adequate management budget support for CMO, assisted by supporting staff/experts in carrying out their duties, serious attention and guarantees for protection from regional heads. In addition, the competence of CMO in East Nusa Tenggara Province consistently needs to be increased in capacity so that they can carry out their duties and authorities more optimally in producing quality, effective and efficient goods/services.